Biomass‐based biomimetic‐oriented Janus nanoarchitecture for efficient heavy‐metal enrichment and interfacial solar water sanitation. Issue 4 (17th August 2022) - Zhao, Hao‐Yu; Dong, Wei‐Xu; Deng, Yu; Chen, Li‐Feng; Zhao, Chen‐Fan; Zhang, Chuan‐Ling; Zhou, Jie; Qu, Yi‐Fan; Li, Yan‐Song; Li, Dong‐Jun; Yu, Shu‐Hong
Abstract: Interfacial solar steam generation (ISSG), involving the use of solar energy to evaporate water at the water‐to‐vapor interface, has presented prospects for the desalination and purification of water due to high energy conversion efficiency and low‐cost freshwater generation. Herein, inspired by the aligned nanostructure of plants for efficiently transporting nutrient ions, we optimally design and construct a biomass‐based Janus architecture evaporator with an oriented nanostructure for ISSG, using the ice template method, followed by biomimetic mineralization with the resource‐abundant and low‐cost biomass of the carboxymethyl cellulose and sodium alginate as the raw materials. Taking advantage of the oriented nanostructure allowing efficient transportation of water and coordination capacity of sodium alginate for effective enrichment of heavy‐metal ions, the biomass‐based Janus architecture shows much lower thermal conductivity and an ultrahigh steam regeneration rate of 2.3 kg m −2 h −1, considerably surpassing those of previously reported oriented biomass‐based evaporators. Moreover, the biomass precursor materials are used for this Janus evaporator, guaranteeing minimum impact on the water ecology and environment during the regeneration process of clean drinking water. This study presents an efficient, green, and sustainable pathway for ISSG to effectively achieve heavy‐metal‐free drinking water. Abstract : A Janus evaporator with a biomass‐based architecture and a biomimetic‐oriented pore nanostructure is constructed for efficient removal of heavy‐metal ions during interfacial solar steam generation by imitating the nanostructures in natural plants. This work presents an effective, green, and sustainable pathway for interfacial solar steam generation to efficiently achieve heavy‐metal‐free drinking water.